Pembaharuan Inovasi dalam Budidaya Pisang serta Pajak Pertambahan Nilainya - Septanta, Rananda; Khuzaeni, Khuzaeni; Arslan, Rijal; Nurhasan, Yunus (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The increasing need for sustainable food sources and economic empowerment in underprivileged communities has become a critical concern, especially in urban areas like South Tangerang. In response, a community service program titled